Variasi dan kekerabatan genetik pada dua jenis baru belimbing (Averrhoa leucopetala Rugayah et Sunarti sp nov dan A. dolichorpa Rugayah et Sunarti sp nov., Oxalidaceae) berdasarkan profil Random Amplified Polymorphic DNA - Yulita, Kusumadewi Sri (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTGenetic variation and relatedness of two new species of star fruit (Averrhoa leucopetalaRugayah et Sunarti sp nov and A. dolichorpa Rugayah et Sunarti sp nov., Oxalidaceae)based on Random Amplified Polymorphic DNA. Two wild species of Averrhoa from Papuaand Gorontalo respectively has recently been described. These two species were previouslytreated as âintermediate speciesâ between A. carambola and A. blimbi on the basis ofmorphological characters. This present study aimed to assess genetic variation and geneticrelatedness of the two species compared to their relatives (A. carambola and A. blimbi) byusing Random Amplified Polymorphic DNA (RAPD). Five RAPD primers (OPA 9E, OPA 13,OPB 7, OPB 18 dan OPN 12) were used to amplify total DNA genom and produced 31 bands towhich 90.32% were polymorphic. These bands were ranging in size from 300-1700 bp. DNAfingeprints for each species was indicated by differences in RAPD profiles resulted fromamplification of five primers. Clustering analysis was performed based on RAPD profilesusing the UPGMA method. The genetic similarity range between 0.25-1.00 indicating widerange of genetic variations observed. Results also indicated that the two species weregenetically distant from A. carambola and A. blimbi, thus supported the recent morphologicaltreatment.Key words: Averrhoa, RAPD profiles, genetic variations.